Quality of Imported Beef in Indonesia - Amam Amam; Haryono Haryono (Universitas Bengkulu, 2021)
Imported beef cattle are cattle (not breeds) imported from abroad to Indonesia, which have superior characteristics to be kept for a certain period to produce meat. The purpose of this research is to explore the quality of imported beef cattle entering Indonesia. The object of the research is beef cattle Breed Brahman Cross, Heifers type as many as 331 heads imported from Australia. The variables observed were Arrival weight (AW), Reweigh (RW), Selling Weight (SW), Weight Difference (WD), Fattening Duration (FD), and Average Daily Gain (ADG). Data analysis used Descriptives Analysis, Bivariate Correlations, and Linear Regression methods with IBM SPSS Statistics tools. The results showed that the lowest AW was 227 kg and the highest was 480 kg; the average weight of the RW results is 354.43 kg; The lowest SW was 361 kg and the highest was 619 kg with an average SW of 481.34 kg; The lowest FD is 70 days and the highest is 109 days; The lowest ADG is 0.62 kg and the highest is 2.43 kg with an average ADG of 1.34 kg. This study concludes that the Selling Weight (SW) of imported beef cattle Breed Brahman Cross-type Heifers is positively and significantly affected by the arrival weight (AW) of 44.6%, Re-weighing (RW) of 52.6%, weight difference (DW) of 18%, and Average Daily Gain (ADG) of 38.3%.